2001
DOI: 10.1021/cm0101430
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Properties of Compounds in the NaHSO4−CsHSO4 System. 2. The Absence of Superprotonic Transitions in Cs2Na(HSO4)3 and CsNa2(HSO4)3

Abstract: Exploratory synthesis in the NaHSO4−CsHSO4 system, aimed at discovering novel proton-conducting solids, yielded the new compounds CsNa2(HSO4)3 and Cs2Na(HSO4)3. Thermal analysis demonstrated the absence of phase transitions for both compounds prior to melting. The conductivities of the two compounds vary monotonically with temperature, in a non-Arrhenius manner, from ambient to the respective melt temperatures of 398 and 413 K. At 363 K the conductivities are on the order of 10-8 Ω1-cm-1, which is comparable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This corroborates earlier hypotheses that large cations generally provide an increased lattice flexibility. 19,75 However, as can be seen in Fig. 6a, the cation size alone is not a sufficient condition for quantitatively relating to flexibility; i.e.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This corroborates earlier hypotheses that large cations generally provide an increased lattice flexibility. 19,75 However, as can be seen in Fig. 6a, the cation size alone is not a sufficient condition for quantitatively relating to flexibility; i.e.…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with our earlier experimental study that observed no superprotonic transition in Cs 2 Na(HSO 4 ) 3 and CsNa 2 (HSO 4 ) 3 and suggested that strong Na–O bonds hinder structural flexibility. 75…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations